Numerical study of flow in a rotor-stator system with inward throughflow - Farzaneh-Gord, M.; Vazifedoost, A.; Khoshnevis, A.B. (Archives of Mechanics, 2010)
A numerical study has been carried out to study fluid flow within a rotor-stator system with an inward throughflow and pre-rotation. Furthermore, the effect of flow parameters on the flow structure has been investigated. The entrainment coefficient, β, of the rotating fluid and the rotating disc moment coefficient have been calculated. A correlation has been found for predicting the place of stagnation point. The results show the Batchelor type of flow with two separated boundary layers on the rotating and stationary discs. The numerical results are compared with the available measured data and generally, a good agreement has been encountered.